57 Weight perception and sociodemographic characteristics following endometrial cancer treatment. (18th September 2019) - Janda, M; Gebski, V; Forder, P; Obermair, A
Abstract : Objectives: To explore the association between self-reported 'unhappiness with weight' and sociodemographic characteristics and weight control behaviors among women who underwent hysterectomy for Stage I endometrial cancer. Methods: Women diagnosed with Stage I endometrial cancer who participated in the Laparoscopic Approach to Cancer of the Endometrium (LACE) trial were invited to complete a five-year follow up survey to evaluate their health status, lifestyle and behaviors including their weight perception and use of weight control methods. Of the 516 eligible patients, 259 (50.2%) agreed to participate in the survey. Results: At follow-up, women who self-reported they were unhappy with their weight were significantly more likely to have an annual income >AUD 40, 000 (ORadjusted 2.7; p=0.025). Women who were unhappy with their weight were more likely to be younger at follow-up compared to women who were happy with their weight (ORadjusted 0.94; p=0.003). Weight loss programs completed in the twelve months prior to completing the survey were strongly predictive of unhappiness with weight; including exercise (ORadjusted 6.3; p<0.001), reduced meal intake (OR 5.2; p<0.001) and reduced fats/sugar intake (OR 5.4; p<0.001). Ever-use of commercial programs and diets from dietary books were also associated with unhappiness with weight at follow-up (p≤0.03). Conclusions: Our study provides evidence that many women continue to be unhappy with weight many years after their endometrial cancer treatment. Supporting their self-directed efforts to lose weight may increase benefit of available programs, and therefore women's satisfaction with current weight.